Development Of Informatics Management Virtual Tour As Digital Information Media Using The Addie Method - Noferianto Sitompul; Vanie Wijaya (Sean Institute, 2022)
Every year, the Sambas State Polytechnic socializes the profiles of its 9 study programs to the public through internet media, video visualization, social media, and PowerPoint slides. The press is considered insufficient, and the community wants media that can interact directly with it, from the campus entrance to the rooms that support learning in each study program. The process of displaying this information is called a Virtual Tour. Because the virtual tour can interact in real-time with the human senses of sight, hearing, and touch, it is thought to be able to communicate information more efficiently. This virtual tour in this study focuses on the Information Management major. The Department at Sambas State Polytechnic has 3 study programs, namely: Informatics Management (D3), Multimedia Engineering (D4), and Corporate Financial Accounting (D4). Because these three study programs experience an increase in the number of new student admissions each year, a new digital information media is needed for these three study programs, which are based on virtual reality to be used when socializing and delivering digital information during study program accreditation. Making this Virtual Reality begins with direct data collection in the form of photos and is designed using the ADDIE development method. The evaluation stage in this method uses a questionnaire for media experts and students majoring in informatics management, calculated using a Likert scale. Material experts are 84.4%, and students, 85.25% of this virtual tour's evaluation results are suitable for digital information media use. It is intended that this virtual tour program may evolve into a virtual tour of the campus of Sambas State Polytechnic.